2015
DOI: 10.1108/jacpr-07-2014-0129
|View full text |Cite
|
Sign up to set email alerts
|

Linking research and practice to address domestic and sexual violence: lessons learned from a statewide conference with researchers and practitioners

Abstract: Purpose-There is a growing emphasis on the need to integrate research and practice in the fields of domestic and sexual violence. However, additional research is needed to identify strategies for key stakeholders to use to bridge research and practice in these areas. The paper aims to discuss these issues. Design/methodology/approach-The current study analyzed qualitative data collected during a statewide conference for researchers and practitioners whose work addresses domestic and/or sexual violence. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 16 publications
(42 reference statements)
0
26
0
Order By: Relevance
“…Studies suggest knowledge translation goals be developed early, in conjunction with, and appropriate for, each target audience group (Beckett et al., 2016; Jack & Tonmyr, 2008; Larrivée, Hamelin‐Brabant, & Lessard, 2012; Murray et al., 2015; Wathen et al, 2010). The goals identified need to be adapted for each target audience, using consistent language to provide the authority required for sustainable outcomes (Jack & Tonmyr, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies suggest knowledge translation goals be developed early, in conjunction with, and appropriate for, each target audience group (Beckett et al., 2016; Jack & Tonmyr, 2008; Larrivée, Hamelin‐Brabant, & Lessard, 2012; Murray et al., 2015; Wathen et al, 2010). The goals identified need to be adapted for each target audience, using consistent language to provide the authority required for sustainable outcomes (Jack & Tonmyr, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Key messages are routinely developed by researchers to share the outcomes of their research, and it is an area well developed in the knowledge translation literature more generally. Much of the literature provides generic examples such as the dissemination of brief evidence‐based, critical, tailored key messages, creating feedback loops, presenting accessible information at formal/informal meetings, education sessions, presenting at national/international conferences and publishing scientific papers (Albers, Mildon, Lyon, & Shlonsky, 2017; Beckett et al., 2016; Boyko, Wathen, & Kothari, 2017; Burke et al., 2013; Connolly et al, 2017; Kothari et al., 2014; Murray, Chow, Chow, Pow, Croxton, & Poteat, 2015; Murray et al., 2015; Nancarrow, 2015; Sibbald, MacGregor, MacMillan, & Wathen, 2017; Tarzia, Humphreys, & Hegarty, 2016; Wathen et al, 2010). Of note is that Murray, Smith, and Avent (2010) found that practitioners read industry publications and attend practice‐based rather than research‐based conferences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations